Starting on the road to pediatric enhanced recovery after surgery: strategies and themes - Sherif Emil; Julia Ferreira; Chantal Frigon; Elena Guadagno; Marcy Horge; Justine Laurie (Elsevier, 2024)
ABSTRACT: Like many innovations in surgery, implementing enhanced recovery after surgery (ERAS) programs in pediatric surgery has lagged behind its adult counterpart. Our institutions have recently made a concerted effort to introduce and implement ERAS widely throughout the Department of Pediatric Surgery, which includes 10 surgical specialties. Our strategy revolved around the early inclusion of all stakeholders, significant educational efforts, and creating a roadmap for development and implementation of ERAS programs. It culminated in the first Canadian pediatric ERAS conference, which was held in Montreal on April 28, 2023, and served as a launching pad for instituting an ERAS culture in our hospital. Throughout the process, we identified specific themes that helped emphasize the rationale for pediatric ERAS programs and kept stakeholders engaged in the efforts. In this paper, we share these strategies and themes, believing they can aid other pediatric institutions seeking to initiate an ERAS culture.Level of evidence: V